PENGGUNAAN GAWAI DAN MEDIA SOSIAL PADA ANAK SEKOLAH DASAR DI JAKARTA UTARA - Irene Rusli; Ellen Wijaya; Diandra Tatiana Gunawan; Andy Setiawan; Felicia Kurniawan (Bahasa Indonesia, 2021)
Background: The growth of gadgets and social media usage among children might affect their physical activity. It shows that high internet usage among elementary school children will incur low physical activity. It is an overweight risk factor for children that might lead into growth and/or development disorder. Methods: Observational analysis with a cross-sectional approach among elementary school children grades 4-6 in North Jakarta with purposive sampling. Physical activity was identified using Physical Activity Questionnaire of Children (PAQ-C). Nutritional status based on examination of height, weight and calculation of body mass index. The analysis was performed using the Spearman correlation test. Results: There were 322 children from 3 different elementary schools in North Jakarta consisting of 136 (42.2%) female and 186 (57.8%) male. Approximately 160 (47.5%) subjects have no parental supervision during gadgets usage and 54 (16.8%) have not had education in regards to the matter. There are 246 (76.3%) subjects have social media account with Facebook as the most frequently use application. Most of subjects (50.3%) using gadgets more than 4 hours per day. There were 256 (79.5%) subjects with low physical activity and 111 (34.5%) overweight children. The gadgets usage duration did not have a significant correlation with body mass index (p>0.05;r=0.21) but had a significant correlation with physical activity (p<0.05;r =0,33). Conclusion: Majority of elementary school children are social media active user and using gadgets with minimal parental supervision and assistance. This circumstance among children has significant correlation with their physical activities.